Synthesis and molecular modeling of MetAP2 of thiosemicarbazides, 1,2,4-triazoles, thioethers derived from (S)-Naproxen as possible breast cancer agents - MEGA TİBER, PINAR; ORUN, OYA (My University, 2022)
© 2022New thiosemicarbazides (3, 5-6), 1,2,4-triazoles (14-15) and thioethers (22-68) from derived (S)-Naproxen were synthesized in this study. The structure of these compounds were elucidated by spectral (FT-IR, 1H NMR, 13C NMR) methods, besides elemental analysis and TLC. The molecular binding of the compounds on MetAP-2 was performed. Anticancer effects of the synthesized compounds were studied by using MTT assay method on MCF-7 (includes oestrogene and progesterone receptors) and MDA-MB-231 (lacks estrogen and progesterone receptors) adenocarcinoma cell lines at 0, 10, 25, 50, 75 and 100 μM concentrations for 24 h. The IC50 values of novel (S)-Naproxen derivatives were determined between from 5 to 100 μM on MCF-7 breast cancer cell line and MDA-MB-231 cell lines. The apoptotic activity of selected compounds 22 and 42 were first analyzed by Annexin V staining using Tali Image-Based Cytometer. Mitochondrial membrane potential changes determined in fluorescence plate reader following JC-1 stain for compounds 22 and 42 in MCF-7 and MDA-MB-231 cells. The effect of these compounds on the cell viability 4T1 mouse mammary tumor cell line was tested at 1 to 5 times of calculated IC50 value (IC50x1, IC50x2, IC50x3, IC50x4, and IC50x5). Next in order to determine the toxicity of the combination of compound 51 and Docetaxel, WST-1 cell viability and proliferation assay was performed with 4T1.
Keywords: Kimya; Analitik Kimya; Biyokimya; Biyoinorganik Kimya; Fizikokimya; Spektroskopi; İnorganik Kimya; Temel Bilimler; Chemistry; Analytical Chemistry; Biochemistry; Bioinorganic Chemistry; Physical Chemistry; Spectroscopy; Inorganic Chemistry; Natural Sciences; Temel Bilimler (SCI); KİMYA, İNORGANİK VE NÜKLEER; KİMYA, ANALİTİK; SPEKTROSKOPİ; KİMYA, ORGANİK; Natural Sciences (SCI); CHEMISTRY; CHEMISTRY, INORGANIC & NUCLEAR; CHEMISTRY, ANALYTICAL; SPECTROSCOPY; CHEMISTRY, ORGANIC; Physical Sciences; Organic Chemistry; Apoptosis; Naproxen; Thioether; Breast cancer cell line; Triple negative cancer; MetAP2; NAPROXEN; ANTICANCER